Descriptive framework for entrepreneur`s capabilities. - Zulkifli, Norzima; Mohd Yusuff, Rosnah; Sorooshian, Shahryar; Ismail, Mohd Yusof (2011)
This paper is a part of an PhD research effort to employ an empirically-based development taxonomy for smaller and medium enterprises (SMEs) aim to develop an understanding framework for the SME potential to success within which governments be able to benchmark and relate it to the benefit to the region to adopt their policies. Data from 321SME entrepreneurs in Iran gathered and attempts to descriptive analyze the Iranian SME entrepreneur’s capabilities.